Chemical Processing Effect on the Tensile Strength of Waste Palm Fiber-Reinforced HDPE Biocomposite: Optimizing Using Response Surface Methodology - Bouyaya, Linda; Belaadi, Ahmed; Boumaaza, Messaouda; Lekrine, Abdelaziz; Chai, Boon Xian; Chetbani, Yazid; Abdullah, Mahmood M. S.; Ghernaout, Djamel; Alshaikh, Ibrahim M. H. (Taylor & Francis, 2024)
This study proposes locally available and environment-friendly Algerian palm (Washingtonia filifera) waste fibers to develop biocomposites. Waste palm fibers (WPFs) were chosen as an effective high-intensity polyethylene (HDPE) reinforcement material to create WPF/HDPE biocomposites. WPFs were treated with sodium hydroxide (NaOH) solution to improve their adhesion to the HDPE matrix. Tensile strength and Youngs modulus were evaluated using mixes generated by the response surface methodology (RSM). Based on RSM, the central composite design was used to investigate the effect of various parameters on the tensile properties of cured WPF/HDPE biocomposites. The tensile properties of cured WPF/HDPE biocomposites were influenced by variables such as NaOH (0-3%), fiber treatment duration (0-24?h), and WPF content (0-30% (wt.)). RSM shows that tensile strength increases significantly with a NaOH concentration of 3%, a fiber treatment duration of 10.12?h, and a maximum content of 30% (wt.) in WPFs. The experimental validation reveals that these values correlate with predicted values with an error of less than 3.55%.